2020
DOI: 10.3390/ijms21062203
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation Is Required for ERK5 Nuclear Translocation and ERK5-Mediated Cancer Cell Proliferation

Abstract: The MAP kinase ERK5 contains an N-terminal kinase domain and a unique C-terminal tail including a nuclear localization signal and a transcriptional activation domain. ERK5 is activated in response to growth factors and stresses and regulates transcription at the nucleus by either phosphorylation or interaction with transcription factors. MEK5-ERK5 pathway plays an important role regulating cancer cell proliferation and survival. Therefore, it is important to define the precise molecular mechanisms implicated i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…All of these findings suggest that CsTLP8 not only functions in transcriptional regulation, but also plays a role in post-transcriptional regulation. This is not unique, as the MAP kinase ERK5 possesses a kinase domain in the NH 2 -terminal region and a transcriptional activation domain and a nuclear localization signal in the COOH-terminal region, allowing this protein to regulate transcription at the nucleus by either phosphorylation or interaction with transcription factors [ 44 ]. In mouse, UBE3A is known as an E3 ubiquitin ligase, which several targets have been identified, UBE3A also functions as a transcriptional regulator of the family of nuclear receptors by interaction with IRF (Interferon Regulatory Factor) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of these findings suggest that CsTLP8 not only functions in transcriptional regulation, but also plays a role in post-transcriptional regulation. This is not unique, as the MAP kinase ERK5 possesses a kinase domain in the NH 2 -terminal region and a transcriptional activation domain and a nuclear localization signal in the COOH-terminal region, allowing this protein to regulate transcription at the nucleus by either phosphorylation or interaction with transcription factors [ 44 ]. In mouse, UBE3A is known as an E3 ubiquitin ligase, which several targets have been identified, UBE3A also functions as a transcriptional regulator of the family of nuclear receptors by interaction with IRF (Interferon Regulatory Factor) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular signal regulated kinase 5 (ERK5) is known to contain a classical BP NLS. Yan et al [25,37] found that the BP NLS ( 505 RKPVTAQERQREREEKR-RRR QERAKEREKRRQERER 539 ) of ERK5 is required for the nuclear targeting of ERK5 upon activation and that this NLS itself is sufficient to drive GFP to the nucleus, indicate that the ERK5 BP NLS is biologically functional.…”
Section: The Classical Nuclear Localization Signals (Cnls)mentioning
confidence: 99%
“…Direct ERK5 activation is classically operated by the upstream MAP2K, MEK5, that has ERK5 as its only known substrate [ 2 ] and phosphorylates ERK5 at Thr218/Tyr220 in the conserved threonine–glutamic acid–tyrosine (TEY) motif of the catalytic domain [ 3 ]. MEK5-dependent phosphorylation stimulates ERK5 nuclear translocation, a key event for the regulation of cell proliferation [ 4 , 5 , 6 ]. In recent years, accumulating evidence points to a relevant role of ERK5 in the onset and progression of several types of cancer, including melanoma [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%